Petualangan ular kata: Linguistic stimulation educational game media early childhood - Rahma, Aulia; Wahyuni, Desvi; Wembrayarli (Al-Athfaal: Jurnal Ilmiah Pendidikan Anak Usia Dini, 2026)
Background: Stimulation of early childhood linguistic intelligence is essential for language development, but there is still limited variety of learning media specifically designed to stimulate the linguistic aspects of children aged 5–6 years. Objective: This study aims to develop and test the effectiveness of the Petualangan Ular Kata game as a medium for stimulating linguistic intelligence for children aged 5–6 years. Method: This study uses the Research and Development method with the ADDIE model, the research involves the stages of analysis, design, development, implementation, and evaluation. Data were collected through expert validation questionnaires, linguistic ability tests (pre-test and post-test), and observation during play activities in 10 children aged 5-6 years. Result: The validation results show that the developed game is declared suitable for use. The effectiveness test showed a significant improvement in children's linguistic skills after the use of the game with a significant difference between pre-test and post-test scores (p < 0.05). Conclusion: The novelty of this study lies in the development of structured language games that have been proven to be effective in stimulating early childhood linguistic intelligence. Petualangan Ular Kata Game has the potential to be an alternative language learning medium in early childhood education.